2019
DOI: 10.1038/s41598-019-42631-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T lymphocyte subsets and related functional molecules in follicular fluid of patients with polycystic ovary syndrome

Abstract: Immune responses play an important role in the pathogenesis of polycystic ovary syndrome (PCOS). However, the characteristics of T lymphocyte subsets in PCOS remain insufficiently understood. In this study, lymphocytes of follicular fluid (FF) were obtained from oocyte retrieval before in-vitro fertilization (IVF) in infertile women with or without PCOS. The levels of cluster of differentiation 25 (CD25), CD69, programmed death 1 (PD-1), interferon-γ (IFN-γ), interleukin 17A (IL-17A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Li et al also show that there is no difference in T between PCOS and controls. 17 Consistent with previous reports, women with PCOS have higher WBC, Neu, and Lym counts than the control group in our study. PCOS shares a state of low-grade inflammation with other non-transmissible chronic diseases, such as obesity, T2DM, and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Li et al also show that there is no difference in T between PCOS and controls. 17 Consistent with previous reports, women with PCOS have higher WBC, Neu, and Lym counts than the control group in our study. PCOS shares a state of low-grade inflammation with other non-transmissible chronic diseases, such as obesity, T2DM, and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that abnormal activation of T cells and cytokine production might lead to the abnormal oocyte development observed in PCOS patients, which was associated with women's infertility. 17,28 A recent study also found that the activation of T cells in PCOS patients with infertility might be suppressed by increased expression of PD-1. IL-10 markedly inhibits the functions of monocytesmacrophages, such as antigen presentation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, researches have focused on the association between immune disorders and PCOS, such as dysfunction of macrophages, dendritic cells and T regulatory cells (Tregs) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Th1 polarization may induce autoimmune diseases including multiple sclerosis, inflammatory bowel disease, rheumatoid arthritis, etc., but Th2-inclination may result in allergic diseases and susceptibility to infection [10,13]. T lymphocyte subsets can be detected by changes in cytokine expression, unique surface markers and nuclear transcription factors [13,14]. The Th1/Th2 balance was found influenced by nutrients, hormones, omega-3 fatty acids, plant sterols/sterolins, particular minerals, probiotics, progesterone and melatonin, suggesting that Th1/Th2-based immunotherapies are promising to date [10].…”
Section: Introductionmentioning
confidence: 99%